HUMAN CAPITAL AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Erlita Kusuma Wardani (Jurnal Ekonomi dan Bisnis Airlangga, 2022)
Introduction: The competitiveness of the workforce in Indonesia is currently still relatively low compared to several ASEAN countries such as Thailand, Malaysia, and Singapore. One of the main factors of this problem is the level of education possessed by the workforce. The construction services sector is a sector that can leverage the country's economy. Thus, the construction sector requires skilled, superior, and reliable workers. The competence and level of education possessed by the workforce will be an important consideration for companies in the construction sector. The purpose of this study is to find out how the influence of Human Capital and Job Satisfaction on Employee Performance.